An effect of hyaluronan as abdominal post-operative anti-adhesive in dogs, macroscopic, laparoscopic and histopathological study: Shatha, M. Hashim and Serwa, I. Salih - Hashim, Shatha M. (The Iraqi Journal of Veterinary Medicine, 2016)
The aim of this study was to evaluate the effectiveness of hyaluronan as abdominal anti-adhesive. Sixteen healthy adult local breed dogs, aged between (1-2 years) and weighed (15-20) kg were used. They were divided into two equal groups. First group is considered as a control group (A), the second group is the hyaluronic acid group (B); both groups underwent celiotomy under the effect of general anesthesia (combination of ketamine-xylazine at the dose rate of 15mg /kg and 5mg/kg B.W, respectively). Three sero-muscular incisions were 3cm long created at anti-mesenteric border in the descending colon and sutured with simple continuous suture using4-0chromic cat gut, abdominal wall closed in routine manner, in control group. The same procedure was performed in group B but 2 ml of 1%sodium hyaluronate was applied intra peritoneally prior to abdominal closure. Evaluation of the results was based on macroscopic, laparoscopic and microscopic examinations. Macroscopic examination showed severe adhesions in all animals in both 7th, 30thpost operative days with high grade scores (grade 3-4), except in one animal there was no adhesion in group A. While in group B, all dogs had developed mild adhesion formation at 7thpost operative day in low grade score (grade, 1). By 30thpost operative day there was no adhesion (grade, zero) except mild adhesion, in one case between omentum and abdominal wall (grade, 1). Histopathological examination showed dense fibrous connective tissue with congested blood vessels and irregular collagen fibersin group A. While in group B there were fine bundles of cellular connective tissue, granulation tissue with mononuclear cells infiltration. There were significant differences (P<0.05) between group B (1.00±0.00) and group A (3.50±0.28) at 7th, also at 30thpost operation a significant difference (P<0.05) was found between group B (*0.25±0.25) and group A (2.75±0.94) macroscopically. Histopathological examination also revealed a significant difference (P < 0.05) between group B(*1.00±0.81)and group A(2.75±0.50) at 7th and 30thpost operative days group B(*1.00±0.81) and group A(2.25±0.95).The study revealed, the effectiveness of hyaluronan in reducing intra-abdominal adhesions that occurred after abdominal surgery in dogs, in comparison with control group.